Monetary-fiscal policy relations in the euro area: The impact on the primary balance - Fabienne Dascher-Preising; Alfred Greiner (Bielefeld University, Faculty of Business Administration and Economics, 2022)
With this paper, our objective is to empirically study public debt sustainability by estimating a fiscal reaction function where the primary balance relative to GDP is assumed to be a function of the public debt to GDP ratio of the previous year and of other macroeconomic variables. In particular, we take into account the effects of monetary policy on the primary budget of the government by including the real long term interest rate and the in ation rate, measured as the change in the GDP price de ator. We resort to the fixed effects and to the random effects models for a panel of 12 euro area economies from 1996 to 2020. We find statistical evidence for sustainable debt policies and detect that both monetary policy variables are positively correlated with the primary balance to GDP ratio. This holds both for the fixed and for the random effects estimation, when those variables are included simultaneously.
urn:nbn:de:0070-pub-29648275
Keywords: E43; E52; E62; E63; H61; H62; H63; 330; Monetary policy; fiscal policy; euro area; primary balance; public debt; sustainability; interest rate; inflation rate